Recreational Physical Activity and Differentiated Thyroid Cancer Risk: A Pooled Analysis of Two Case-Control Studies. Issue 2 (21st July 2016) - Xhaard, Constance; Lence-Anta, Juan J.; Ren, Yan; Borson-Chazot, Françoise; Sassolas, Geneviève; Schvartz, Claire; Colonna, Marc; Lacour, Brigitte; Danzon, Arlette; Velten, Michel; Clero, Enora; Maillard, Stéphane; et al.
Abstract : Purpose: Physical activity has been hypothesized to influence cancer occurrence through several mechanisms. To date, its relation with thyroid cancer risk has been examined in relatively few studies. We pooled 2 case-control studies conducted in Cuba and Eastern France to assess the relationship between self-reported practice of recreational physical activity since childhood and thyroid cancer risk. Methods: This pooled study included 1, 008 cases of differentiated thyroid cancer (DTC) matched with 1, 088 controls (age range 9-35 and 17-60 years in the French and Cuban studies, respectively). Risk factors associated with the practice of recreational physical activity were estimated using OR and 95% CI. Logistic regressions were stratified by age class, country, and gender and were adjusted for ethnic group, level of education, number of pregnancies for women, height, BMI, and smoking status. Results: Overall, the risk of thyroid cancer was slightly reduced among subjects who reported recreational physical activity (OR = 0.8; 95% CI 0.5-1.0). The weekly frequency (i.e. h/week) seems to be more relevant than the duration (years). Conclusion: Long-term recreational physical activity, practiced since childhood, may reduce the DTC risk. However, the mechanisms whereby the DTC risk decreases are not yet entirely clear.